A Comparison between QLAB and TomTec Full Volume Reconstruction for Real Time Three-Dimensional Echocardiographic Quantification of Left Ventricular Volumes. - Soliman OI; Krenning BJ; Geleijnse ML; Nemes A; van Geuns RJ; Baks T; Anwar AM; Galema TW; Vletter WB; Ten Cate FJ (Echocardiography, 2007)
Objectives: To compare the interobserver variability and accuracy of two different real time three-dimensional echocardiography (RT3DE) analyzing programs. Methods: Forty-one patients (mean age 56 +/- 11 years, 28 men) in sinus rhythm with a cardiomyopathy and adequate 2D image quality underwent RT3DE and magnetic resonance imaging (MRI) within one day. Off-line left ventricular (LV) volume analysis was performed with QLAB V4.2 (semiautomated border detection with biplane projections) and TomTec 4D LV analysis V2.0 (primarily manual tracking with triplane projections and semiautomated border detection). Results: Excellent correlations (R(2) > 0.98) were found between MRI and RT3DE. Bland-Altman analysis revealed an underestimated LV end-diastolic volume (LV-EDV) for both TomTec (-9.4 +/- 8.7 mL) and QLAB (-16.4 +/- 13.1 ml). Also, an underestimated LV end-systolic volume (LV-ESV) for both TomTec (-4.8 +/- 9.9 mL) and QLAB (-8.5 +/- 14.2 mL) was found. LV-EDV and LV-ESV were significantly more underestimated with QLAB software. Both programs accurately calculated LV ejection fraction (LV-EF) without a bias. Interobserver variability was 6.4 +/- 7.8% vs. 12.2 +/- 10.1% for LV-EDV, 7.8 +/- 9.7% vs. 13.6 +/- 11.2% for LV-ESV, and 7.1 +/- 6.9% vs. 9.7 +/- 8.8% for LV-EF for TomTec vs. QLAB, respectively. The analysis time was shorter with QLAB (4 +/- 2 minutes vs. 6 +/- 2 minutes, P < 0.05). Conclusions: RT3DE with TomTec or QLAB software analysis provides accurate LV-EF assessment in cardiomyopathic patients with distorted LV geometry and adequate 2D image quality. However, LV volumes may be somewhat more underestimated with the current QLAB software version.